Elements of influence for solar ventilated building facades: a review. Issue 1 (May 2021) - Sima, C; Teodosiu, C; Fokone, A T; Bejan, A S
Abstract: Climate change has become a fundamental concern for scientific researchers, architects and engineers, so it's required to improve the performance of sectors responsible for city and building infrastructure. Burning fossil fuels to produce electricity and heat is the biggest cause of climate change and emissions, and represents one third of total greenhouse gas emissions. Thus, buildings become responsible for improving the external environment, either by construction phase, rehabilitation process or by maintainability process. This work reviews and evaluates elements of influence for solar ventilated building facades in order to improve this field of research as this solution allows to achieve important energy savings.